Strategic Usability and Response in Ecommerce Marketing: A Framework and Investigation - Richardson, Paul; Choong, Peggy (Journal of Applied Business and Economics, 2023)
In the literature usability is presented as an objective standard to which firms aspire to assist in the consumer decision-making process. In this paper, we introduce the concept of strategic usability, which we define as the variation of usability components to influence mindset formation and response that are most desired by the firm. We further illustrate how laws of UX design identified in the literature can impact usability components in different ways to influence response. A strategic usability framework is then presented and examined using preliminary data collected from Amazon.com. Results suggest that firms can indeed implement strategic usability to heighten motivation and response to the offers most desired by the firm and minimize response and interactions towards those less desired. However, such a strategy can pose risks for the firm. Implications for consumer welfare and accessibility are discussed.